HIV Associated Psoriasis-A Clinical Study - Singh Ajit; Thappa Devinder Mohan; Hamide Abdoul (Wolters Kluwer Medknow Publications, 1999)
Six cases of HIV associated psoriasis were found out of 75 HIV infected patients with various mucocutaneous disorders. All of them were male and their mean age was 42.3 year. Psoriasis was diagnosed at presentation in five case, however, in one it was diagnosed after 1 year of having been detected as HIV seropositive. The mean age at onset of psoriasis was 42 years. Psoriasis vulgaris occurred in 3 cases whereas two had psoriatic eryroderma and one had palm plantar psoriasis. Five of our patients were in group III of HIV disease and only one was in group II. To conclude, psoriasis may be the first manifestation of HIV infection.